2018
DOI: 10.1007/s10637-018-0560-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, dose-escalation study of PF-06664178, an anti-Trop-2/Aur0101 antibody-drug conjugate in patients with advanced or metastatic solid tumors

Abstract: Purpose and Methods Trop-2 is a glycoprotein over-expressed in many solid tumors but at low levels in normal human tissue, providing a potential therapeutic target. We conducted a phase 1 dose-finding study of PF-06664178, an antibody-drug conjugate that targets Trop-2 for the selective delivery of the cytotoxic payload Aur0101. The primary objective was to determine the maximum tolerated dose and recommended phase 2 dose. Secondary objectives included further characterization of the safety profile, pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Two examples of ADCs in clinical development that use warheads that inhibit topoisomerase I activity include trastuzumab deruxtecan targeting HER2 in breast and gastric cancers and sacituzumab govitecan targeting Trop2 in breast and lung cancers (22,23). A Biologics License Application has been filed for sacituzumab govitecan for metastatic triple-negative breast cancer, and trastuzumab deruxtecan is currently in multiple late-stage pivotal clinical trials.…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two examples of ADCs in clinical development that use warheads that inhibit topoisomerase I activity include trastuzumab deruxtecan targeting HER2 in breast and gastric cancers and sacituzumab govitecan targeting Trop2 in breast and lung cancers (22,23). A Biologics License Application has been filed for sacituzumab govitecan for metastatic triple-negative breast cancer, and trastuzumab deruxtecan is currently in multiple late-stage pivotal clinical trials.…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
“…In a phase I trial in third-line triple-negative breast cancer, sacituzumab govitecan demonstrated an ORR of 31% and a median progression-free survival of 5.5 months (Table 1). In this trial, sacituzumab govitecan was dosed at 10 mg/kg on days 1 and 8 every 21 days and showed improved tolerability compared with other ADCs targeting Trop2 such as PF-06664178, which had a MTD of 2.4 mg/kg, showed limited efficacy, and was terminated due to high toxicity (23).…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
“…This section focuses on two anti-TROP-2 ADCs that have been studied clinically, sacituzumab govitecan, using the topoisomerase inhibitor, SN-38 (an irinotecan metabolite) [ 66 , 99 107 ], and another agent, RN927C, coupled to a derivative of the microtubule inhibitor, auristatin [ 108 , 109 ]. Other TROP-2-targeted therapeutics have been described preclinically, one using a nanoparticle (carboxymethyl dextran) carrier linked with doxorubicin, which has activity in the MDA-MB-231 breast cancer cell line representative of TNBC [ 110 ], and another, utilizing doxorubicin conjugated to an anti-TROP-2 Fab, with activity in vitro and in vivo against pancreatic cancer [ 111 ].…”
Section: Antibody-drug Conjugates (Adcs)mentioning
confidence: 99%
“…A phase I clinical trial with this ADC was performed in 31 patients with a variety of metastatic epithelial cancers [ 109 ]. Nineteen of the patients provided tissue samples for TROP-2 expression, with 13 (68%) having medium to high expression (i.e., ≥50% of tissue cells having 2+ to 3+ staining).…”
Section: Antibody-drug Conjugates (Adcs)mentioning
confidence: 99%
“…In order to achieve sufficient efficacy with a relatively low DAR number, potent payloads such as PBD, a MDR1-resistant maytansine payload, and an auristatin payload Aur0101 have been developed. However, the DAR 2 site-specific conjugates with PBD and Aur0101 have shown limited therapeutic index in clinic thus far [173][174][175][176], while the clinical data for the DAR 2 maytansine ADC is pending [177]. While extensive characterization studies have been reported for antibody conjugated to cytotoxic payloads, there is a scarcity of literature on the molecular properties of conjugates with non-toxic small organic molecule payloads and nucleic acids.…”
Section: Conjugate Developability Formulations and Characteristicsmentioning
confidence: 99%